The impact of arts on prescription on individual health and wellbeing: a systematic review with meta-analysis - Anita Jensen; Anita Jensen; Nicola Holt; Sayaka Honda; Hilary Bungay (Frontiers Media S.A., 2024)
IntroductionThe evidence-base for the impact of participating in the arts for different aspects of health and wellbeing is growing. Arts on Prescription has gained increasing recognition as a method for fostering connections among individuals and communities, however, to date no systematic review of the impact on individual health and wellbeing has been conducted. This review aims to provide an understanding of individual health and wellbeing outcomes from participation in Arts on Prescription programmes.MethodsMajor electronic databases were systematically searched, including Cochrane Library; Web of Science; ProQuest; CINAHL; Arts & Humanities; Ebsocohost; Pubmed; PsycINFO. Other databases were also used: Google Scholar and websites of specific organizations, e.g., NHS Evidence, Kings Fund, Health foundation, Nuffield Trust and NESTA and University of Florida Arts-in Medicine Repository. The review used PRISMA reporting structures. Critical Appraisal Skills Programme (CASP) templates were used for qualitative and quantitative studies, and the Mixed Methods Appraisal Tool (MMAT) for studies with a mixed methods protocol to assess quality and risk of bias. A narrative review of the qualitative data was conducted. For quantitative outcomes, a meta-analysis for studies that met inclusion criteria was conducted, and a narrative review made of secondary and heterogeneous outcomes and approaches.Results7,805 records were identified but only 25 records were included as studies with a focus on the impact on individual health and wellbeing. Studies were conducted in Australia, Denmark, Sweden, United Kingdom, and the United States. Programmes were held in community settings, arts venues, GP surgeries, primary healthcare settings, and one school. Most interventions varied from 8 to 10 weeks and included a wide range of different arts activities. Qualitative themes included social benefits, psychological benefits and progression opportunities. The meta-analysis showed a statistically significant improvement in wellbeing, and the narrative review identified promising outcomes that require further evidential support (e.g., reductions in anxiety and depression).DiscussionArts on Prescription programmes are an appropriate intervention for improving psychosocial wellbeing, providing both social and psychological benefits as well as progression opportunities. We discuss the various qualitative and quantitative outcomes, along with potential 'active ingredients' and barriers to participation (physical, psychological and social).Systematic review registrationPROSPERO, identifier CRD42023408974, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023408974.